Immunological and homeostatic pathways of alpha -1 antitrypsin: a new therapeutic potential - Mazzuca, Carmen; Vitiello, Laura; Travaglini, Silvia; Maurizi, Fatima; Finamore, Panaiotis; Santangelo, Simona; Rigon, Amelia; Vadacca, Marta; Angeletti, Silvia; Scarlata, Simone (Frontiers in Immunology, 2024)
α -1 antitrypsin (A1AT) is a 52 kDa acute-phase glycoprotein belonging to the serine protease inhibitor superfamily (SERPIN). It is primarily synthesized by hepatocytes and to a lesser extent by monocytes, macrophages, intestinal epithelial cells, and bronchial epithelial cells. A1AT is encoded by SERPINA1 locus, also known as PI locus, highly polymorphic with at least 100 allelic variants described and responsible for different A1AT serum levels and function. A1AT inhibits a variety of serine proteinases, but its main target is represented by Neutrophil Elastase (NE). However, recent attention has been directed towards its immune-regulatory and homeostatic activities. A1AT exerts immune-regulatory effects on different cell types involved in innate and adaptive immunity. Additionally, it plays a role in metal and lipid metabolism, contributing to homeostasis. An adequate comprehension of these mechanisms could support the use of A1AT augmentation therapy in many disorders characterized by a chronic immune response. The aim of this review is to provide an up-to-date understanding of the molecular mechanisms and regulatory pathways responsible for immune-regulatory and homeostatic activities of A1AT. This knowledge aims to support the use of A1AT in therapeutic applications. Furthermore, the review summarizes the current state of knowledge regarding the application of A1AT in clinical and laboratory settings human and animal models.